2023
DOI: 10.1007/s40273-023-01300-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Age-Specific Values for Pediatric HRQoL in Cost-Effectiveness Analysis: Is There a Problem to Be Solved? If So, How?

Abstract: Value sets for the EQ-5D-Y-3L published to date appear to have distinctive characteristics compared with value sets for corresponding adult instruments: in many cases, the value for the worst health state is higher and there are fewer values < 0. The aim of this paper is to consider how and why values for child and adult health differ; and what the implications of that are for the use of EQ-5D-Y-3L values in economic evaluations to inform healthcare resource allocation decisions. We posit four potential explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In part, this links to wider methodological questions: should age-specific instruments be accompanied by age-specific value sets, and if not, what other alternatives exist? [ 45 ] On the basis of significant differences in development and life stage, one expects that the stated preferences of adults for the health of 2- to 4-year-olds might be different than that of a 10-year-old (which is the current age used in the Y-3L value-set protocol). However, emerging research has shown minimal impact on values when framed by different child ages.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this links to wider methodological questions: should age-specific instruments be accompanied by age-specific value sets, and if not, what other alternatives exist? [ 45 ] On the basis of significant differences in development and life stage, one expects that the stated preferences of adults for the health of 2- to 4-year-olds might be different than that of a 10-year-old (which is the current age used in the Y-3L value-set protocol). However, emerging research has shown minimal impact on values when framed by different child ages.…”
Section: Discussionmentioning
confidence: 99%